Euthanasia via CO2 inhalation causes premature cortical granule exocytosis in mouse oocytes and influences in vitro fertilization and embryo development. Issue 7 (13th May 2019) - Wuri, Liga; Agca, Cansu; Agca, Yuksel
Abstract: Generation of high quality mouse metaphase II oocytes is an integral part for efficient in vitro fertilization (IVF), and subsequent embryo production for reproductive studies and genome banking. The main objectives of this study were to investigate the impact of various euthanasia methods on IVF, embryo development, and subcellular structures of MII mouse oocytes. Following superovulation regimen, female mice were euthanized by high flow CO2 (H CO2 ), low flow CO2 (L CO2 ), or cervical dislocation (CD). The MII oocytes obtained from these mice were evaluated for subcellular integrity by assessing their cortical granules and F‐actin. Furthermore, fertilization and subsequent embryonic development competence up to blastocyst stage were also evaluated in vitro. The oocytes collected from females euthanized by CD resulted in significantly higher two‐cell development rates ( p = 0.028) and subsequently lead to in higher embryo development rates ( p = 0.027) compared with oocytes from females euthanized by L CO2 . The cortical granule integrity analysis revealed significantly higher rate of premature cortical granules exocytosis (PCGE) for L CO2 group compared with CD and H CO2 groups ( p < 0.001). These data collectively suggest that CO2 associated PCGE during euthanasia procedure is the main cause of decreased IVF rates and CD is the optimal euthanasia method for the purpose of obtaining good quality MII oocytes for mouse IVF and other reproductive studies. Abstract : The main objectives of this study were to investigate the impact of various euthanasia methods on in vitro fertilization (IVF), embryo development, and subcellular structures of MII mouse oocytes. This study clearly demonstrated that cervical dislocation (CD) euthanasia method was able to preserve the intact distribution of cortical granules (CGs) and F‐actin of MII mouse oocytes with significantly higher two‐cell embryo development, and morula and blastocyst formation rate compared with the either H CO2 or L CO2.